The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/2632352420980456
|View full text |Cite|
|
Sign up to set email alerts
|

Memorialisation during COVID-19: implications for the bereaved, service providers and policy makers

Abstract: Background: The aim of this rapid perspective review is to capture key changes to memorialisation practices resulting from social distancing rules implemented due to the ongoing COVID-19 pandemic. Method: As published peer-reviewed research pertaining to memorialisation practices during the COVID-19 pandemic is lacking, this rapid review includes academic literature from the pre-COVID-19 period and international media reports during the pandemic. Findings: Changes to memorialisation practices were under way be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 31 publications
1
35
0
8
Order By: Relevance
“… Lay See Khoo 34 Malaysia Journal article Review Necessary guidelines should be provided for all corpse management steps, including the temporary burial of the bodies of unidentified migrants and refugees, especially when dealing with mass corpses. Jennifer Lowe 35 Australia Journal article Review The COVID-19 pandemic has caused changes in memorial ceremonies, such as in contact with corpses, funerals, and burials. These changes are likely to remain in place even in the post-corona area.…”
Section: Resultsmentioning
confidence: 99%
“… Lay See Khoo 34 Malaysia Journal article Review Necessary guidelines should be provided for all corpse management steps, including the temporary burial of the bodies of unidentified migrants and refugees, especially when dealing with mass corpses. Jennifer Lowe 35 Australia Journal article Review The COVID-19 pandemic has caused changes in memorial ceremonies, such as in contact with corpses, funerals, and burials. These changes are likely to remain in place even in the post-corona area.…”
Section: Resultsmentioning
confidence: 99%
“…This has required funeral directors to adapt to new circumstances which can change rapidly by using videoconferencing or livestreaming technology, although this has been inconsistent ( MacNeil et al, 2021 ; Selman et al, 2021 ). For some, the ritual of viewing the body at a funeral home has been substituted with the coffin taken around the streets for people to acknowledge the death ( Lowe et al, 2020 ) as reported in our study.…”
Section: Discussionmentioning
confidence: 99%
“…13 Dying is seen as a time of poignancy and intimacy for family, 13 highlighting the importance of bedside vigils, in-person farewells and family involvement in preparing the body. 43 Even when social and familial practices are re-shaped by legal, behavioural and social interventions designed to contain an infectious disease outbreak, 43 family members' desires to maintain these practices do not cease. Disruptions to rituals before and after death and a lack of social support compounds family members' grief.…”
Section: Discussionmentioning
confidence: 99%